Insuficiencia suprarrenal por everolimus: a propósito de un caso clínico - Hernández Navas, Jorge Andrés (2025)
Although rare, secondary adrenal insufficiency represents a serious complication in patients receiving treatment with mTOR inhibitors, such as everolimus. This drug is commonly used to prevent organ transplant rejection and to treat certain cancer types, but its impact on adrenal function is not always apparent. In the case presented, a 74-year-old man with a history of liver transplant and type 2 diabetes mellitus attended his routine medical check-up with no symptoms related to adrenal insufficiency. Despite his asymptomatic state, the medical team decided to study adrenal function because of the prolonged duration of everolimus treatment. The diagnostic tests included the measurement of 24-hour urine cortisol, which revealed low cortisol levels, thus confirming adrenal insufficiency. This finding is significant, as adrenal insufficiency can result in adrenal crises that, if not properly managed, can be potentially fatal. This case highlights the importance of endocrine surveillance in immunosuppressed patients, where the absence of symptoms should not lead to complacency. A proactive approach to evaluating adrenal function is crucial for identifying complications before they become emergencies. Early detection and appropriate treatment of adrenal insufficiency can significantly improve clinical outcomes and the quality of life for these patients. Therefore, it is recommended that physicians remain vigilant to the risks associated with the use of mTOR inhibitors and conduct regular adrenal function evaluations in this patient group.